ACCOUNTING TREATMENT OF INVENTORY TRANSACTIONS IN PT. SOLINDO TAMA JAYA BUDURAN SIDOARJO - Aprilya, Awita; Puspitaningrum Dewi Kartika, Titis (IQTISHADequity jurnal MANAJEMEN, 2023)
Inventory is important for manufacturing companies. Inventories require proper management, recognition, measurement, recording and valuation, so that the company can provide useful information for evaluation and internal control. The purpose of this study is to identify the suitability of SAK-ETAP implementation of inventories in manufacturing companies. This research was conducted at one of the manufacturing companies engaged in the sponge industry, namely PT. Solindo Tama Jaya Branch Buduran Sidoarjo. In this study the data analysis technique used was descriptive qualitative using 2 (two) data sources, namely primary data and secondary data. Data collection techniques in this study used the method of observation (observation), interviews (interviews), and documentation. Based on the research that has been done, it can be concluded that the inventory accounting treatment at PT. Solindo Tama Jaya Branch Buduran Sidoarjo complies with SAK-ETAP in force in Indonesia. Conformity is reflected in the recognition, measurement, recording, assessment, and presentation of financial statements that are in accordance with the principles of SAK-ETAP